1999
DOI: 10.1021/np990138z
|View full text |Cite
|
Sign up to set email alerts
|

New Fish Feeding Deterrents, Including a Novel Sesquiterpenoid Heterogorgiolide, from the Brazilian Gorgonian Heterogorgia uatumani (Octocorallia, Gorgonacea)

Abstract: Studies of the Brazilian gorgonian octocoral Heterogorgia uatumani have resulted in the discovery of two metabolites that inhibit fish feeding under natural conditions. These are the previously reported eunicellane diterpenoid, (6E)-2alpha,9alpha-epoxyeunicella-6, 11(12)-dien-3beta-ol (1) and a new sesquiterpene lactone, heterogorgiolide (2). The structures of 1 and 2 were determined by spectroscopic methods and by comparison of spectral data with literature values. Field bioassays of the two compounds, at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 32 publications
0
29
0
1
Order By: Relevance
“…Organic extracts of gorgonians do not appear to have strong antimicrobial activity against marine bacteria (Jensen et al 1996). The most common hypothesis is that secondary metabolites are anti-predatory agents, and studies have consistently demonstrated antipredatory properties of gorgonian crude extracts and purified compounds (Pawlik et al 1987, Fenical & Pawlik 1991, Pawlik & Fenical 1992, Maia et al 1999, Koh et al 2000.…”
Section: Abstract: Gorgonian · Chemical Defense · Physical Defense ·mentioning
confidence: 99%
“…Organic extracts of gorgonians do not appear to have strong antimicrobial activity against marine bacteria (Jensen et al 1996). The most common hypothesis is that secondary metabolites are anti-predatory agents, and studies have consistently demonstrated antipredatory properties of gorgonian crude extracts and purified compounds (Pawlik et al 1987, Fenical & Pawlik 1991, Pawlik & Fenical 1992, Maia et al 1999, Koh et al 2000.…”
Section: Abstract: Gorgonian · Chemical Defense · Physical Defense ·mentioning
confidence: 99%
“…Recently, the sesquiterpene heterogorgiolide 74 and a known eunicellane diterpenoid 75 from Heterogorgia uatumani were reported to be unpalatable to natural assemblages of fishes in Brazil. 265 A similar study of the endemic Brazilian gorgonian Lophogorgia violacea using field feeding assays for bioassay-guided fractionation yielded a mixture of 5 furanocembranoid diterpenes that appear to deter fish predation in an additive manner. 267 Crude extracts from common species of gorgonians collected in the Caribbean, 281 " 282 Singapore, 283 and the Pacific, 270 ' 284 have been surveyed for predator deterrent activity in laboratory assays against a generalist predator or in field assays against natural assemblages of reef fishes.…”
mentioning
confidence: 99%
“…Recently, the sesquiterpene heterogorgiolide 74 and a known eunicellane diterpenoid 75 from Heterogorgia uatumani were reported to be unpalatable to natural assemblages of fishes in Brazil. 265 A similar study of the endemic Brazilian gorgonian Lophogorgia violacea using field feeding assays for bioassay-guided fractionation yielded a mixture of 5 furanocembranoid diterpenes that appear to deter fish predation in an additive manner. 267 This mixture included two new furanocembranoids, 7-acetoxy-hydroxylophotoxin 76 and 3-methoxy-8-hydroxylophotoxin 77 and the known compounds, lophotoxin 78, deoxylophotoxin 79 and 13-acetoxy-11P, 12P-epoxypukalide 80.…”
mentioning
confidence: 99%